Collection and storage of DNA-containing biomaterial and isolated DNA - Yu. V. Doludin; A. S. Limonova; V. A. Kozlova; A. I. Efimova; A. L. Borisova; A. N. Meshkov; M. S. Pokrovskaya; O. M. Drapkina (Кардиоваскулярная терапия и профилактика)
The advances of biomedicine include the new technologies, diagnosis and treatment techniques, as well as the practical use of new types of biological targets, in particular, nucleic acids. Genomic deoxyribonucleic acid (DNA), extracellular DNA (exDNA) and microbiome DNA obtained from different types of samples (tissues, blood and its derivatives, feces, etc.) are used as objects of genetic research. The use of new technologies for DNA analysis required the development of standardized methods for processing biological samples in order to obtain high-quality DNA samples. The research uses various methods for collecting, preparing samples and storing various DNA-containing biomaterials and isolated DNA, as well as methods for assessing the quality of samples and biobank standards. It is obvious that the use of uniform standards will allow large-scale genetic research on the basis of biobanks and research laboratories. Specialists from professional organizations such as International Society for Biological and Environmental Repositories (ISBER), Biobanking and BioMolecular Resources Research Infrastructure-European Research Infrastructure Consortium (BBMRI-ERIC), European, Middle Eastern & African Society for Biopreservationa and Biobanking (ESBB) and the Russian National Association of Biobanks and Biobanking Professionals.